PEMANFAATAN SUDUT BACA KELAS SEBAGAI PENGUATAN BUDAYA LITERASI DALAM MEWUJUDKAN GENERASI BERKARAKTER, BERWAWASAN LUAS DAN BERPIKIR KRITIS : Pemanfaatan Sudut Baca Kelas Sebagai Penguatan Literasi Siswa - Nadia Nur Hanifah; Puspita, Meila Narta Eka; Putri, Tessa Ayudiya; Zahra, Chayla Nur Auliatus; Yani, Muhammad Turhan (Universitas Negeri Surabaya (Unesa), 2026)
Literacy skills are an important foundation in shaping character, broadening horizons, and fostering critical thinking skills in students. However, the low level of student literacy in Indonesia is still a challenge that needs to be overcome through effective and sustainable strategies. One effort that can be made is through the use of class reading corners as a means of encouraging reading habits that are fun and easily accessible. This article aims to examine the urgency of literacy culture in schools, the implementation of class reading corners, and supporting and inhibiting factors in their implementation. The method used is a literature study of various relevant scientific sources. The results of the study show that class reading corners play an important role in increasing reading interest, forming positive student character, expanding knowledge horizons, and honing critical thinking skills. The success of utilizing reading corners is greatly influenced by teacher involvement, the availability of interesting reading materials, and support from the school and family environment. With optimal management, reading corners can become the main pillar in building a strong literacy culture in schools. Keywords: literacy, class reading corners, character, insight, critical thinking